MECHANICAL AND MORPHOLOGICAL PROPERTIES OF PP/PE COMPOSITE FISHING NET ROPES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study examined how the extrusion process, which is affected by different thermal settings, and the raw material sources, composed of various polypropylene (PP) and polyethylene (PE) blends with or without calcium carbonate (CaCO3) additives, influence the quality and mechanical properties, such as tensile strength, elongation, and stiffness, of composite ropes for fishing net production. A comparative analysis of extrusion process parameters was conducted among four distinct extruders from the Promatech, Miyachi, Sima, and Ichikawa companies with a focus on their thermal settings, characterized by varying the temperature profiles. The investigation was extended to the utilization of PP derived from different sources and granule compositions, including formulations with CaCO3 additives. In terms of breaking force, the samples with CaCO3 showed an average increase of 5.2% when compared to those without CaCO3. With the addition of CaCO3, the elongation at break increased by an average of 8.7%. The addition of CaCO3, surprisingly, resulted in a slight decrease in stiffness, averaging a decrease of 2.1% when compared to the samples without CaCO3. Most significantly, the addition of CaCO3 resulted in a significant decrease in Young's modulus, with an average reduction of approximately 66.4% compared to the samples without CaCO3. This study reveals substantial differences in rope mechanical quality due to variations in raw materials and extrusion parameters, emphasizing the need for adapting the manufacturing process to consistently produce high-quality composite ropes for knitting fishing nets.